2003
DOI: 10.1016/j.ehj.2003.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Closed-Loop Stimulation, overdrive pacing, DDDR pacing mode on atrial tachyarrhythmia burden in Brady-Tachy Syndrome A randomized study

Abstract: CLS pacing was associated with a significantly lower AT burden,compared to the other pacing algorithms. Moreover APP was significantly higher in DDD+ and in CLS mode, than in DDDR. APP weakly correlated with AT burden only in DDD+ mode, though the lowest AT burden level was obtained in the CLS group where no significant correlation was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Recently, a new physiological rate‐responsive pacemaker has been developed, based on the indirect measure of ventricular contractility: the Closed Loop Stimulation (CLS). Studies performed on the adult population have verified both the efficacy of the pacemaker to modulate heart rate during different stress and the clinical advantages in the treatment of some pathologies, 18–23 but no data are available on the behavior of such pacing strategy in younger patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new physiological rate‐responsive pacemaker has been developed, based on the indirect measure of ventricular contractility: the Closed Loop Stimulation (CLS). Studies performed on the adult population have verified both the efficacy of the pacemaker to modulate heart rate during different stress and the clinical advantages in the treatment of some pathologies, 18–23 but no data are available on the behavior of such pacing strategy in younger patients.…”
Section: Introductionmentioning
confidence: 99%
“…7) Puglisi A et al evaluated the suppressive effect of three kinds of pacemaker rate-responsive algorithms on PAf, including conventional response, overdrive pacing and CLS modes, and found that the CLS mode effectively suppressed PAf for 4 and 7 months after PMI. 6) They inferred that turbulent autonomic Figure 2 Memory data obtained from pacemaker Based on memory data obtained from pacemaker clinic, the rates of ventricular and atrial pacing and atrial sensing more rapid than 150 bpm as surrogate marker of atrial fibrillation are shown. The on-and-off prophylactic effect of CLS against PAf attacks was obvious during hospitalization after PMI.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, this rate-adaptive mode was shown to be possibly effective in suppressing paroxysmal atrial tachycardia burden. 6) However, as far as we are aware, there are few case reports which showed that CLS mode had obvious benefit in preventing paroxysmal atrial fibrillation (PAf) in SSS patients, even with antiarrhythmic agents. We observed distinct immediate and longterm effectiveness of CLS mode along with drug administration in preventing frequently repetitive development of PAfs in an SSS case.…”
mentioning
confidence: 99%
“…Both of these were expected to prevent development of PAF. [3][4][5][6] A lower rate was then set at 55 bpm ( Figure 1). AV delay was set to the rate-dependent (Dynamic) AV delay again.…”
Section: Case Reportmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] However, there are few detailed reports concerning the effective management of atrioventricular (AV) interval for suppression of PAF which develops after implantation of a DDD pacemaker (PM) with the current standard functions of rate-response and MVP.…”
mentioning
confidence: 99%